A study on swine flu (H1N1) awareness among college students of Valsad city - Baria, Hinal Govind; Solanky, Priti; Shah, Hitesh; Patel, Ravikant (International Journal Of Community Medicine And Public Health, 2017)
Background: The aims were to study knowledge, perceptions and beliefs regarding swine flu among college students and to study any difference in knowledge between science and commerce students. Methods: A cross sectional study conducted in Science and Commerce College of Valsad city from June-July 2015. Simple random sampling technique used. Total 400 students were randomly selected from both the colleges. The study was started after obtaining the verbal and informed consent from both the college authorities whereas verbal and informed consent was taken from each student. Data collection done by using predesigned, pretested, bilingual language (English and Gujarati) semi structured questionnaire. Students who were present and had given consent to participate in the study been included and those who are absent and not willing to participate are excluded from study. Data were presented in percentages and p value was calculated by Chi-square test. Results: 63.18% and 53.73% commerce, 86% and 84.5% science knows causative agent and other name of swine flu respectively and difference is statistically highly significant. More than 60% of science and commerce students reported cough/sneezing as modes of transmission. 57% science and 40% commerce correctly answer symptoms of swine flu. Television (>35%) was major source of information in both groups. Conclusions: Although students are aware of swine flu but correct knowledge about swine flu is lacking in both the groups. Knowledge regarding key points such as frequent hand washing, avoiding crowding places, vaccine and treatment availability, which is much important during epidemics and pandemics as precautionary measures, was lacking in both the groups.